Urban Expansion in The Erbil City and Its Impact on The Drinking Water Use Production - Aziz Qadir Aziz; Sulaiman Ismail Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The city of Erbil, like any other region, is expanding because of the growing population, which has played a significant role in the production and use of drinking water. The aim of the research is to highlight the directions of erbil's population growth, the expansion of erbil city and the influence on use between 1950 and 2020, for this purpose, the number of neighborhoods has been taken as a measure during which time the number of neighborhoods in the year (2003-2010) reached 74 neighbourhoods, as well as the amount of water produced by Efraz water (1.2.3) and erbil city wells numbering 292 wells, the average water production reached (16,380) square meter per hour, but the amount of yield swells One person reached about 100 litres a day, but in 2010-2020 the number of neighbourhoods in Erbil increased to 152 neighbourhoods, the amount of water produced in all three water projects. Efraz (1,2.3) and erbil's wells, which number 920, have reached drinking water production (25644114) Square meter in one hour and individual consumption has reached 400 litres of water in one day.